2018
DOI: 10.3389/fpsyg.2018.00527
|View full text |Cite
|
Sign up to set email alerts
|

Novice Shooters With Lower Pre-shooting Alpha Power Have Better Performance During Competition in a Virtual Reality Scenario

Abstract: Competition changes the environment for athletes. The difficulty of training for such stressful events can lead to the well-known effect of “choking” under pressure, which prevents athletes from performing at their best level. To study the effect of competition on the human brain, we recorded pilot electroencephalography (EEG) data while novice shooters were immersed in a realistic virtual environment representing a shooting range. We found a differential between-subject effect of competition on mu (8–12 Hz) o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 15 publications
3
17
0
Order By: Relevance
“…The analysis of theta power, alpha power, and beta power within the last three seconds before trigger pull revealed the effects of these strategies. Consistent with Pereira's report, our study did not find consistent differences in EEG power for competition in the groups [ 27 ], which could be because the subjects in this work were professional shooters, and the two groups had similar skill levels and could have the same neurocognitive strategies. However, we found the differences between the competitive and noncompetitive states.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The analysis of theta power, alpha power, and beta power within the last three seconds before trigger pull revealed the effects of these strategies. Consistent with Pereira's report, our study did not find consistent differences in EEG power for competition in the groups [ 27 ], which could be because the subjects in this work were professional shooters, and the two groups had similar skill levels and could have the same neurocognitive strategies. However, we found the differences between the competitive and noncompetitive states.…”
Section: Discussionsupporting
confidence: 88%
“…Some researchers have proposed that competition changes the environment for athletes [ 27 ], and from the point of view of improving motor performance, the neural basis underlying competition has been studied by using different methods. Among them, in 2014, Antonis et al proposed a self-talk intervention for competitive sport performance and reported that the performance of the group participating in self-talk is significantly improved compared to the control group, which provides a new direction for the study of improving motor performance in a competitive environment [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Frontal alpha EEG was recorded in a study of its role in attentional control; the study also demonstrated the importance of the immersion and engagement afforded by a 3D virtual learning environment (Berger and Davelaar, 2018). In a study of the effect of competition, while shooters were immersed in a virtual environment representing a shooting range, changes in alpha oscillatory activity were found during aiming that were associated with better performance (Pereira et al, 2018). In a previous study by the authors (Muñoz et al, 2016b), frontal alpha activity (as well as delta) was found to be a brainwave pattern that allows differentiation between baseline and active shooting states in a VR simulator.…”
Section: Related Workmentioning
confidence: 98%
“…Our second example combines a BCI with another technology covered in this paper, namely VR. Pereira et al ( 2018 ) investigated EEG correlates of realistic training and competition scenarios while novice shooters were immersed in a 10 m Olympic pistol shooting environment. In the training scenario, shooters remained alone; while in the competition scenario there were other competitors and an audience.…”
Section: Brain-computer Interfaces and Brain Stimulationmentioning
confidence: 99%